2003
DOI: 10.1103/physreve.67.047601
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear stability of solitons against strong external perturbations

Abstract: We study soliton stability under the action of strong external perturbations. Limits on the weak perturbation approach are established with the help of average Lagrangian methods and full simulations. We found that for the same relative perturbation, larger amplitude solitons develop instability earlier than weaker amplitude solitons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Note that unlike the previous exponential ansatz of Ref. [15], the present one preserves accurately the structure of equilibrium solutions. To obtain governing equations for the ansatz variables, called collective variables, we adopt the variational approach.…”
Section: The Model and Low-dimensional Equationsmentioning
confidence: 79%
See 1 more Smart Citation
“…Note that unlike the previous exponential ansatz of Ref. [15], the present one preserves accurately the structure of equilibrium solutions. To obtain governing equations for the ansatz variables, called collective variables, we adopt the variational approach.…”
Section: The Model and Low-dimensional Equationsmentioning
confidence: 79%
“…In a recent work soliton stability against nonintegrable effects has been investigated [15]. However, proper motion of soliton centroid has not been considered as in all the analyzed cases solitons were taken as vibrating envelopes centered at fixed points.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma radio emissions generated by Langmuir-ion acoustic turbulence through nonlinear three-wave interactions (Melrose, 1991;Chian and Abalde, 1995;Rizzato et al, 2003) have been observed in planetary foreshocks (Kuncic and Cairns, 2005), type-III solar radio bursts (Lin et al, 1986;Henri et al, 2009) and type-II radio bursts from interplanetary shocks (Ledenev et al, 2008). A schematic diagram depicting the emission of nonthermal radio emissions by nonlinear wave-wave interactions in plasmas, via either a Langmuir-Alfvén turbulence or a Langmuirion acoustic turbulence, is shown in Fig.…”
Section: Chaos In the Planetary-exoplanetary Environmentmentioning
confidence: 98%
“…1 shows that nonthermal radio emissions can be produced via a Langmuir-ion acoustic turbulence. This three-wave interaction involves an electron-beam driven Langmuir wave (L), a transverse electromagnetic wave (T) and an ion-acoustic wave (S), which is represented as L T AE S (Melrose, 1991;Chian and Abalde, 1995;Rizzato et al, 2003). It provides an emission mechanism for nonthermal radio emissions in planetary foreshocks and interplanetary medium (Lin et al, 1986;Kuncic and Cairns, 2005;Henri et al, 2009).…”
Section: Chaos In the Planetary-exoplanetary Environmentmentioning
confidence: 98%
See 1 more Smart Citation